2023
DOI: 10.1002/adhm.202202668
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Structured Hydroxyapatite Particles Facilitate the Enhanced Integration and Selective Anti‐Tumor Effects of Amphiphilic Prodrug for Osteosarcoma Therapy

Abstract: Efficient delivery of cargo into target cells is a formidable challenge in modern medicine. Despite the great promise of biomimetic hydroxyapatite (HA) particles in tissue engineering, their potential applications in bone tumor therapy, particularly their structure–function relationships in cargo delivery to target cells, have not yet been well explored. In this study, biomimetic multifunctional composite microparticles (Bm‐cMPs) are developed by integrating an amphiphilic prodrug of curcumin with hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Hydroxyapatite (HA) is the primary inorganic component of human bone and has excellent biocompatibility, osteoconductivity, and osteoinductivity [18]. Its diverse applications include hard tissue repair [19,20], drug delivery [21,22], and anti-tumour interventions [23][24][25]. Previous studies have demonstrated that PLGA treated with HA can enhance hydrophilicity, neutralise the acidic microenvironment arising from PLGA degradation, and increase surface roughness, potentially enhancing cell adhesion [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HA) is the primary inorganic component of human bone and has excellent biocompatibility, osteoconductivity, and osteoinductivity [18]. Its diverse applications include hard tissue repair [19,20], drug delivery [21,22], and anti-tumour interventions [23][24][25]. Previous studies have demonstrated that PLGA treated with HA can enhance hydrophilicity, neutralise the acidic microenvironment arising from PLGA degradation, and increase surface roughness, potentially enhancing cell adhesion [26,27].…”
Section: Introductionmentioning
confidence: 99%